THE EFFECT OF STUDENT FACILITATOR AND EXPLAINING LEARNING MODEL ON SPEAKING SKILLS OF FOURTH GRADE STUDENTS AT SDN SUDIMARA 12 SOUTH TANGERANG - Fairus Sintawati; Ratih Ayu Wulandari; Peni Astuti; Ulinuha Dahlina; Desty Endrawati Subroto (Peneliti.net, 2019)
This study aims to determine the effect of the Student Facilitator and Explaining Learning Model on English speaking skills. This study uses a quantitative approach and the type of research used is a quasi-experimental research. The population of this study was the fourth-grade students of MI Darul Ulum, totaling 54 students, while the sampling technique was carried out with a saturated sample, namely the entire population was sampled. Based on the results of research and data analysis of students who were taught by applying the Student Facilitator and Explaining learning model, it affected the speaking skills of the fourth-grade students of MI Darul Ulum. This can be proven with a significant level = 0.05. From this value, it is obtained that tcount > ttable is 3.492 > 0.013, then Ho is rejected and H1 is accepted. So, it can be concluded that through the application of the Student Facilitator and Explaining learning model students can improve speaking skills in the fourth grade of MI Darul Ulum